IDENTIFICATION OF COMPOUNDS IN SOURSOP LEAVES (Annona muricata L) AS BREAST ANTICANCER AGAINST ALFA ESTROGEN RECEPTORS BY MOLECULAR DOCKING - Muhammad Fauzi; Nur Aini; Auliana Auliana; Syarifah Rugayah; Ciara Fitri Pribadi; Rizki Rahmadi Pratama (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
The incidence of breast cancer in Indonesia is steadily rising. Women have the highest incidence of breast cancer. Acetogenins are highly effective inhibitors of mitochondrial complex I or NADH dehydrogenase, making them a promising option for therapeutic creation against breast cancer. The plant known as Annona muricata, also referred to as the soursop leaf plant, is purported to possess the ability to suppress the activity of breast cancer. Hence, it is imperative to assess the chemical composition of soursop leaves on receptors by docking experiments. Research utilizing the active site on the alpha estrogen receptor has determined that the reticulin molecule, with a free energy of -8.14 kcal/mol, is a potential contender for breast cancer therapeutic medications. Reticulin exhibits the highest affinity for binding to the active site of estrogen receptor alpha. This chemical exhibits the capacity to impede the growth of breast cancer.